<meta http-equiv="refresh" content="1; url=/nojavascript/"> Multi-Step Equations with Like Terms ( Read ) | Algebra | CK-12 Foundation
Dismiss
Skip Navigation
You are viewing an older version of this Concept. Go to the latest version.

Multi-Step Equations with Like Terms

%
Best Score
Practice Multi-Step Equations with Like Terms
Practice
Best Score
%
Practice Now

Multi-Step Equations with Like Terms

What if you had an equation in which the same variable appeared twice, like 2(x - 4) + 4x =-23 ? How could you simplify the equation so that the variable appears only once in order to solve for it? After completing this Concept, you'll be able to combine like terms to solve two-step equations like this one.

Watch This

CK-12 Foundation: 0305S Combining Like Terms in Two-Step Equations

Guidance

When we look at a linear equation we see two kinds of terms: those that contain the unknown variable, and those that don’t. When we look at an equation that has an x on both sides, we know that in order to solve it, we need to get all the x- terms on one side of the equation. This is called combining like terms . The terms with an x in them are like terms because they contain the same variable (or, as you will see in later chapters, the same combination of variables).

Like Terms Unlike Terms
4x, 10x, -3.5x, and \frac{x}{12} 3x and 3y
3y, 0.000001y, and y 4xy and 4x
xy, 6xy, and 2.39xy 0.5x and 0.5

Example A

To add or subtract like terms, we can use the Distributive Property of Multiplication.

3x + 4x &= (3 + 4)x = 7x \\0.03xy - 0.01xy &= (0.03 - 0.01)xy = 0.02xy\\-y + 16y + 5y &= (-1 + 16 + 5)y = 10y\\5z + 2z - 7z &= (5 + 2 - 7)z = 0z = 0

To solve an equation with two or more like terms, we need to combine the terms first.

Example B

Solve (x + 5) - (2x - 3)=6 .

There are two like terms: the x and the -2x (don’t forget that the negative sign applies to everything in the parentheses). So we need to get those terms together. The associative and distributive properties let us rewrite the equation as  x + 5 - 2x + 3 = 6 , and then the commutative property lets us switch around the terms to get x - 2x + 5 + 3 = 6 , or (x - 2x) + (5 + 3) = 6 .

(x - 2x) is the same as (1 - 2)x , or -x , so our equation becomes -x + 8 = 6

Subtracting 8 from both sides gives us -x = -2 .

And finally, multiplying both sides by -1 gives us x = 2 .

Example C

Solve \frac{x}{2} - \frac{x}{3} = 6 .

This problem requires us to deal with fractions. We need to write all the terms on the left over a common denominator of six.

\frac{3x}{6} - \frac{2x}{6} = 6

Then we subtract the fractions to get \frac{x}{6} = 6 .

Finally we multiply both sides by 6 to get x = 36 .

Watch this video for help with the Examples above.

CK-12 Foundation: Combing Like Terms in 2 Step Equations

Vocabulary

  • Terms with the same variable in them (or no variable in them) are like terms. Combine like terms (adding or subtracting them from each other) to simplify the expression and solve for the unknown.

Guided Practice

Solve \frac{2x}{5} - \frac{3x}{2} = 11 .

This problem requires us to deal with fractions. We need to write all the terms on the left over a common denominator of ten.

\frac{4x}{10} - \frac{15x}{10} = 11

Then we subtract the fractions to get -\frac{11x}{10} = 11 .

Finally we multiply both sides by -\frac{10}{11} :

-\frac{11x}{10}\cdot -\frac{10}{11} = 11 \cdot -\frac{10}{11}

to get x = -10 .

Practice

Solve the following equations for the unknown variable.

  1. 1.3x - 0.7x = 12
  2. -10a - 2(a+5) = 14
  3. 5(2y-3y) = -20
  4. \frac{2}{3}x - \frac{1}{5}x = \frac{14}{15}
  5. 5x - (3x + 2) = 1
  6. s - \frac{3s}{8} = \frac{5}{6}
  7. 10(y + 5y) = 10
  8. 2.3x+2(0.75x-3.5) = 7.5
  9. 3(x+2)+5(2-x)=-32
  10. 6x + 2(5x - 2) = 12

Image Attributions

Reviews

Email Verified
Well done! You've successfully verified the email address .
OK
Please wait...
Please wait...

Original text